SYST-04 PRELIMINARY REPORT OF A CLINICAL TRIAL EVALUATING THE SAFETY AND EFFICIENCY OF NEOADJUVANT CAMRELIZUMAB AND APATINIB IN PATIENTS WITH RECURRENT HIGH-GRADE GLIOMAS: A PROSPECTIVE, PHASE II, SINGLE-ARM STUDY. (5th August 2022) - Lin, Fuhua; Guo, Chengcheng; Yang, Qunying; Chen, Yinsheng; Ke, Chao; Sai, Ke; Zhang, Ji; Jiang, Xiaobing; Hu, Wanming; Xi, Shaoyan; Zhou, Jian; Li, Depei; et al.
Abstract: High-grade glioma is the most common malignant primary brain tumor in the central nervous system. Multiple strategies such as surgery, radiotherapy, and chemotherapy have been used, but the prognosis of patients with high-grade glioma remains poor. No standard treatment exists for recurrent gliomas; however, combination therapies of programmed cell death protein 1 blockades with antiangiogenic agents have demonstrated promising effects in different solid tumors. We have initiated a clinical trial designed to evaluate the safety and efficiency of neoadjuvant therapy using camrelizumab and apatinib in patients with recurrent highgrade gliomas. In this prospective, Phase II, singlearm study, patients with recurrent highgrade gliomas will receive singledose intravenous injection of camrelizumab (200 mg) and daily oral administration of apatinib (250 mg/day for 7 days) 14 days before surgery for recurrent tumor. Sequential therapy will begin 2 weeks after surgery with the biweekly injection of camrelizumab and 4 weeks after surgery with the daily administration of apatinib. Treatment of camrelizumab and apatinib will be continued until disease progression or unacceptable toxicity or death. The trial is planned to enroll 30 patients. Up-to date (March 31, 2022), 12 patients had been enrolled, in which, 9 were GBM. Three patients died, while 4 cases on trial more than 6 months, the longest already 1 year. Although an evaluation is still impossible to be conducted yet, some patients have shown a promising outcome. We will present updated results on the meeting. These preliminary data suggest that this study would be worthwhile. This study was approved by the Ethics Committee of Sun Yatsen University Cancer Center (Guangzhou, China; approval No. SLB202014901). This study was registered with ClinicalTrials.gov under identifier NCT04588987.